Les entreprises innovatrices et leur performance dans le domaine de l’exportation - Hanel, Petr; Palda, Kristian (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractThe analysis presentd in this paper aim at determining to what degree the R & D activity of a firm contributes to its propensity to export, considering the other potential factors that might influence its international competitiveness. This analysis is based on data resulting from a recent investigation on innovation made by De MeIto for the Economic Council of Canada.